Access to Legal Aid for Underprivileged People Based on Law No. 16 of 2011 concerning Assistance - Fanni, Aurelia Grace; Clarissa, Nikita; Ive, Ive; Nagari, Vistanasia Kundalini; Aureta, Viola; Sangkaeng, Vallexa (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research examines the implementation of legal aid for underprivileged communities based on Law Number 16 of 2011 concerning Legal Aid. Access to justice is a fundamental right of every citizen guaranteed by the constitution; however, many underprivileged people still face difficulties in obtaining legal assistance due to financial limitations. Data from the Central Statistics Agency shows that the number of poor people in Indonesia still reaches 26.50 million people in 2022, and this condition is exacerbated by the lack of public knowledge about their right to receive free legal aid. This study raises three research questions: the implementation of legal aid programs for underprivileged communities in Indonesia, the obstacles faced in program implementation, and efforts to optimize the legal aid program. Using a normative juridical method through statutory and conceptual approaches, this research is expected to make a significant contribution to developing a more effective and accessible legal aid system for underprivileged communities.